THE ABILITY OF CONTRAST-ENHANCED ULTRASOUND IN THE DIAGNOSIS OF LIVER METASTASES IN CERVICAL CANCER - V. S. Kryazheva; M. A. Chekalova; Z. R-B. Musaeva; V. V. Kuznetsov (ABV-press, 2017)
Objective: to explore the possibilities of contrast-enhanced ultrasound (CEUS) in the diagnosis of liver metastases in patients with a diagnosis of cervical cancer.Materials and methods. We analyzed the results of 4 clinical cases, of which 3 cases according CEUS diagnosed with liver metastases, in 1 case - nodular hyperplasia.Results and conclusions. Despite the small number of observations, we have concluded that the use of CEUS allows to expand possibilities of the ultrasound method in the differential diagnosis of focal changes in the liver.